Premieren '84 : 30 Kölner Galerien und die Museen der Stadt Köln. - Galerie Baecker, Köln; Baukunst-Galerie, Köln; Galerie Thomas Borgmann, Köln; Galerie Dreiseitel, Köln; Galerie Gugu Ernesto, Köln; Anna Friebe Galerie, Köln; Galerie Glöckner, Köln; Galerie Gmurzynska, Köln; Galerie Karsten Greve, Köln; Galerie Hermes, Köln; Galerie Max Hetzler, Köln; Galerie Heinz Holtmann, Köln; et al. (Köln : Stadt Köln, 1984)
Anderle, Jiri ; Baselitz, Georg ; Simon, Paco ; Glantzman, Judith ; Greenblat, Rodney Alan ; Arntz, Gerd ; Tschinkel, August ; Kippenberger, Martin ; Mields, Rune ; Kallin-Fischer, Grit ; Haring, Keith ; Nattermüller, Ulrike ; Antes, Horst ; Trockel, Rosemarie ; Jahns, Rudolf ; etc.
Premieren '84 : 30 Kölner Galerien und die Museen der Stadt Köln, 3. - 5.5.84
boek